A TRIZ Approach to Reliable Megaproject Sustainability - Chen, Zhen; Agapiou, Andrew; Li, Heng; Xu, Qian (Frontiers in Built Environment, 2021)
Purposes: This paper presents a recent research into megaproject sustainability with a particular focus on identifying a structure of its body of knowledge so as to establish the methodology of megaproject assessment on sustainability (MAS), which consists of a research roadmap towards megaproject sustainability and a system reliability analysis. In response to the Research Topic on ‘Reviews for Advanced Construction Management’ at Frontiers in Built Environment, this paper aims to make a contribution with the description about a generic approach to conducting literature review based on a whole range of relevant evidence in a systemic way. Methodology: The research described in this paper is underpinned by the use of several methods. The nine-square process (NSP) of TRIZ (Theory of Inventive Problem Solving) is the method to facilitate a systemic evidence-based learning (EBL) process to identify further research into MAS. A normal process to establish research roadmap was then introduced to summarize what has been identified as specific research tasks alongside lifecycle processes on megaproject delivery, to which RIBA Plan of Work 2020 was adopted as the prototype. An event tree analysis (ETA) was eventually introduced by incorporating the novel measurements on system reliability in order to support quantitative MAS in terms of both practices and research. Findings: This paper presents several findings from the described research, and these include that the use of NSP led to the formation of a systematic procedure for literature review, a procedure to support MAS, a research roadmap to facilitate efforts to be made for megaproject sustainability, the feasibility to use system reliability in measuring the status of sustainability underpinned by research and practices throughout megaproject lifecycle. Implications: The described research provides four modules to foster further research into megaproject sustainability, and these include a TRIZ based module to facilitate systemic literature review for EBL, a lifecycle process module for MAS, a prototype research roadmap to guide research and development for megaproject sustainability, and an ETA module to support a system reliability analysis in the dynamic process of research and practices towards megaproject sustainability.